Selfcare and quality of life in the elderly - Ochoa Rivera, Janela Nicole; Sangacha Yugsi, Anderson Jose (Enfermería Cuidándote, 2025)
Introduction: Self-care constitutes a fundamental axis in the stage of old age. Older adults who maintain their independence and autonomy usually have a better perception of their general wellbeing. Objective: To determine the level of self-care and quality of life in older adults attending the Centro Integral de Atención Geriátrica del Cantón Salcedo. Methods: Cross-sectional analytical study, with a population of 59 users, from which a sample of 41 participants was obtained. The Self-Care Agency Assessment Scale and the WHOQOL-OLD test were used, which addressed 6 dimensions, applied in October 2024. Results: Of the 41 older adults, 68.3% presented a low level of self-care. General quality of life was rated as moderately good by 48.8% and good by 48.8% of the participants, which indicated a similar distribution between both ratings; the dimension of death and dying obtained a score above the mean of 3.51, while the dimension of intimacy had the lowest score of 2.67. On the other hand, a moderate direct correlation of 0.589 was found, determining that the higher the level of self-care, the better the participants’ perception of quality of life. Conclusion: Despite limitations in self-care including the presence of illness and lack of emotional support, older adults have managed to find satisfaction and well-being in other aspects of their lives.